Controle social: um exercício possível nas instâncias deliberativas das políticas sociais no Brasil em tempos de avanço neoliberal e neoconservador? - Santos, Maria Suelen (2025)
This work aims to analyze the contradictions for the materialization of social control in the deliberative instances of social policies after the advance of neoconservatism in Brazil. Institutional deliberative and participatory spaces are part of the process of bourgeois democratization which, resulting from the class struggle, fuels the expectation of segments of the working class to exercise societal control over the State, social policies, and public funds. The method used for the proposed research corresponds to dialectical-historical materialism. The study is conducted through exploratory, bibliographical research with a qualitative approach. Data collection involves a literature review of Marxist authors on the topic of participation, democracy, the State, civil society, and social control, and a documentary survey on social participation in deliberative bodies during the Jair Bolsonaro administration. The collected data were systematized based on a document analysis guide that guided the reading of the documents for later analysis. It is understood that to guarantee the continuous flow of capital and its territorial dominance in a context of crisis, the mechanisms of bourgeois democratization, although structurally limited, enter into crisis, and are disregarded and threatened by the autocratic, authoritarian and reactionary State, revealing in the neoliberal context, the deepening of the destructive aspect of capital. Advances from deliberative bodies to social policies are important, materializing through the resistance of struggles and the political and historical strength of workers amidst the traits of Brazilian political culture. However, setbacks with the advance of the extreme right also need to be carefully observed, revealing the limits of the institutional democracy of social control. Furthermore, it is understood that social participation as part of democratic social control needs to be linked to the radical struggle for workers, with the hegemonic direction being the transformation of the current order.